Attitudes of the Iraqi Public towards the Propaganda Logic of Terrorist Organizations - خضير سعد محمد (ALBAHITH ALALAMI, 2015)
The research entitled "the attitudes of Iraqi People towards the Logic Propaganda for Terrorist Organization such as Daash Regulation, as-Qaida, and Jabhat al-Nasra". It is a field study on the professors and the students of the College of Mass Media at Baghdad University in 2014. After the global war on terrorism declared on September 11, 2011, the researcher finds it is important to study such subject as it threats the unity and sovereignty of Iraq especially after the invasion of Daash regulation of parts of its lands. This research is a descriptive one. The researcher has used the "questionnaire form" to show the results and to express their digital implications. Propaganda addresses firstly the emotions of people and secondly their minds. The terrorist organizations exploit the emotional side as an essential pillar to achieve their goals especially in a crisis of a sectarian character. Daash regulation represents religious extremism on the Iraqi society. It threats peace and security in the Arab Homeland; its philosophy is non-religious in order to break up the Arabs and Muslim world particularly its funding sources are international funding. It also uses different styles of propaganda to convince the public and create an environment of sectarian through violence and power (force) among the components of Iraqi society. Daash regulation depends on electronic media more than the traditional one due to its quickly spread and easily browsed by most people. One of the most important reasons behind the decline of this regulation is the formation of the popular crowd troops to support the Iraqi armed forces.